Effect of Semiarid Environment on Some Nutritional and Antinutritional Attributes of Calendula (Calendula officinalis) - Muhammad Iqbal; Iqbal Hussain; Asma Habib; Muhammad Arslan Ashraf; Rizwan Rasheed (Journal of Chemistry)
Stressful environments have been shown to affect the metabolism in some plants. In the present study, we assessed whether semiarid environment (saline and saline alkaline soil) could affect the nutritional (total proteins, phenolics and riboflavin contents, and catalase activity) and antinutritional (hydrogen peroxide and malondialdehyde contents) properties differently in different plant parts (leaves, flowers, and roots) of calendula. Although salinity decreased plant biomass, it did not affect total protein and phenolics contents in the calendula. All plant parts were rich in riboflavin contents. However, plants grown under saline-alkali soil had relatively more riboflavin contents in the flowers. Salinity increased hydrogen peroxide (H2O2) concentration in the flowers and roots, whereas saline-alkali soil did not affect it. Plants exposed to both saline and saline-alkali soil had greater catalase activity in the flowers and leaves. Plants exposed to salinity had higher malondialdehyde (MDA) contents in the flowers compared with nonsaline and saline-alkali conditions. Nonetheless, the possibility of safely using different parts of calendula as nutraceutical was in the order flower > root > leaf. Overall, the results suggested that plant can be grown in mild saline-alkali (EC ≤ 7; pH = 8.5) soils without affecting its nutraceutical properties.